Search for short- and long-lived axion-like particles in H → a a → 4 γ decays with the ATLAS experiment at the LHC - Aad, G; Abbott, B; Abeling, K; Abicht, NJ; Abidi, SH; Aboulhorma, A; Abramowicz, H; Abreu, H; Abulaiti, Y; Acharya, BS; Bourdarios, CA; Adamczyk, L; et al. (SpringerOpen, 2024)
Presented is the search for anomalous Higgs boson decays into two axion-like particles (ALPs) using the full Run 2 data set of 140fb-1 of proton-proton collisions at a centre-of-mass energy of 13TeV recorded by the ATLAS experiment. The ALPs are assumed to decay into two photons, providing sensitivity to recently proposed models that could explain the (g-2)μ discrepancy. This analysis covers an ALP mass range from 100 to 62GeV and ALP-photon couplings in the range 10-7TeV-1<Caγγ/Λ<1TeV-1, and therefore includes signatures with significantly displaced vertices and highly collinear photons. No significant excess of events above the Standard Model background is observed. Upper limits at 95% confidence level are placed on the branching ratio of the Higgs boson to two ALPs in the four-photon final state, and are in the range of 10-5 to 3×10-2, depending on the hypothesized ALP mass and ALP-photon coupling strength.